(S[UJOAXRRLMRPROLMJ ELRLMJVJ(B: (SASRZAVFLV FSFPEYVF]Ps - (SAuxlmjw Df}ugc(Slrw Ss (Interbooks, 2002)
(SFLVAD]DJ [UJOAXRRLMRPROLMR SFULBANNRP ELA[URPLMJ AQLA [UJOAXRV FSFPEYVFLV VF SADLA VXRL[FLA VF VYPKJMFV BFBALRXJXAV FSFPEYVFLV VF SADLA VXRL[FLA VF VYPKJMFV ABFBALRXJXAV KF]ULA [AUXRZYNAMLRYs
(SFLVAD]DJ [UJOAXRRLMRPROLMR SFULBANNRP ELA[URPLMJ AQLA [UJOAXRV FSFPEYVFLV VF SADLA VXRL[FLA VF VYPKJMFV BFBALRXJXAV FSFPEYVFLV VF SADLA VXRL[FLA VF VYPKJMFV ABFBALRXJXAV KF]ULA [AUXRZYNAMLRYs